Effectiveness Of Game-Based Learning Methods - Muda, Amelia; Jassin, Iwan (JCI Publisher, 2025)
This study aims to evaluate the effectiveness of game based-learning methods in improving students’ learning motivation in elementary schools.In this digital era,the use of technology in education is increasing,including the integration of educational games as a learning tool. This method is expected to make the teaching and learning process more interestin and interactive,so that it can also increase students’ learning motivation. This study uses a quantitative approach with an experimental design to measure changes in students’ learning motivation before and after implementation of game based-learning methods.